Sacred natural sites classification framework based on ecosystem services and implications for conservation. Issue 4 (29th January 2022) - Ma, Jianzhong; Tam, Christine; Li, Tianjiang; Yu, Guangzhi; Hu, Guanghui; Yang, Feiling; Wang, Junjun; Wu, Ruidong
Abstract: Sacred natural sites (SNSs) are examples of community‐level governance for sustainable management of natural resources, which can greatly benefit nature conservation. However, the lack of a comprehensive understanding of the role of SNSs in conservation has resulted in overly simplistic classifications of SNSs that challenge current SNS research and conservation practice. Here, we propose an SNS classification framework based on the types and levels of material and spiritual services that SNSs provide, and applied this framework in the Khawa Karpo, an important sacred area in the Tibetan region of China based on detailed field surveys conducted from 2000 to 2004 and 2015 to 2017 that addressed six types of SNSs, including sacred mountains, Ri Vgag s, sacred lakes, sacred rocks, sacred caves, and sacred trees. We found that SNSs in this region played a crucial role in sustaining traditional cultures and providing material services. Adoption of our classification framework will assist with the development of management strategies and targeted conservation actions for individual SNSs, thus improving conservation levels particularly in the Tibetan region. Abstract : We proposed a classification framework for sacred natural sites (SNSs) based on the analysis of the relationships between people and nature from an ecosystem services perspective. Different management or conservation schemes should be implemented for different categories of SNSs. Classifying SNSs based on ecosystem services should be a key precondition for integrating them into conservation practices.